Translating and piloting a cardiovascular risk assessment and management online tool using mobile technology - Monica Zolezzi; Athar Elhakim; Taimaa Hejazi; Lana Kattan; Dana Mustafa; Shimaa Aboelbaha; Shorouk Homs; Yazid N. Al Hamarneh (Elsevier, 2023)
Background: Cardiovascular disease (CVD) risk assessment and management (RAM) services face many challenges and barriers in the community. Mobile technology offers the opportunity to empower patients and improve access to health prevention strategies to overcome these barriers. However, there is limited information on the availability and use of CVDRAM-related mobile technology in the Arabic language. Objectives: To pilot test an Arabic version of a CVDRAM application among potential end-users accessing community pharmacy services in Qatar. Methodology: Translation of an established cardiovascular risk calculator (EPI·RxISK™) into the Arabic language was conducted. The English/Arabic version of the calculator was tested by potential end-users, consisting of a sample of community pharmacists (CRxs) and members of the public (MOP) accessing community pharmacy services. Semi-structured interviews were conducted based on the quality attributes of the Mobile Application Rating Scale (MARS). Data were analyzed using deductive content analysis. Results: A total of 10 CRxs and 5 MOP were interviewed. Five themes emerged to describe the EPI·RxISK™ calculator: Engagement, Functionality, Attractiveness, Education, and Responsiveness. For the most part, positive subthemes were associated with each of these themes. The functionality and educational themes had some negative subthemes. Conclusion: End-users of the EPI·RxISK™ calculator had mostly positive descriptors that were aligned with all five quality attributes of the web and mobile applications.